Comparison of CATCH, PECARN and CHALICE rules in children with minor head trauma. - Ferhatlar, Mehmet Esat; Cumhur, Bilgehan Ahmet; Koca, Yavuzselim; Bozan, Oner; Kalkan, Asim (European Journal of Trauma & Emergency Surgery, 2026)
Purpose: The aim of this study is to prospectively compare the diagnostic performance of the PECARN, CATCH, and CHALICE clinical decision rules in pediatric patients presenting with minor head trauma, within a rural secondary-level emergency department characterized by limited resources, high patient volume, and restricted access to specialist physicians. Methods: The study was designed as a prospective observational study. The PECARN, CATCH, and CHALICE clinical decision rules were applied to the patients included in the study, and the data were recorded. The data included in the study were statistically analyzed using the SPSS (Statistical Package for Social Sciences; SPSS Inc., Chicago, IL) 27 program. A value of p < 0.05 was considered statistically significant. Results: A total of 1,032 patients were included in the study. The PECARN did not miss any of the 15 patients with pathological brain CT and had 100% sensitivity and 52.1% specificity. CATCH failed to detect pathological brain CT in 1 patient and had 93.3% sensitivity and 53.3% specificity. CHALICE failed to detect pathological brain CT in 2 patients, with 86.7% sensitivity and 87.8% specificity. Overall, PECARN was more successful in detecting pathological brain CT, but it also had a high false-positive brain CT rate. Conclusion: PECARN criteria are more sensitive than other criteria in predicting brain CT pathology, but they lead to a large number of brain CT scans. While the CHALICE criteria are beneficial in reducing unnecessary brain CT scans, they may miss positive cases.